Just War and Reason of State in Mary Jesus of Ágreda - Martín Gómez, María (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
In the 17th century, the Conceptionist nun Sister Mary of Jesus of Ágreda and the Spanish King Philip IV began an epistolary correspondence in which they discussed philosophical and political issues of various kinds. This article analyses their application of the philosophical concepts of ‘just war’ and ‘reason of state’ in order to safeguard an already declining Catholic monarchy.
Keywords: Mary Jesus of Ágreda; Felipe IV; Just War; Reason of State